TiO2 hollow spheres composed of highly crystalline nanocrystals exhibit superior lithium storage properties - Zhang, Genqiang (2014)
While the synthesis of TiO2 hollow structures is well-established, in most cases it is particularly difficult to control the crystallization of TiO2 in solution or by calcination. As a result, TiO2 hollow structures do not really exhibit enhanced lithium storage properties. Herein, we report a simple and cost-effective template-assisted method to synthesize anatase TiO2 hollow spheres composed of highly crystalline nanocrystals, in which carbonaceous (C) spheres are chosen as the removable template. The release of gaseous species from the combustion of C spheres may inhibit the growth of TiO2 crystallites so that instead small TiO2 nanocrystals are generated. The small size and high crystallinity of primary TiO2 nanoparticles and the high structural integrity of the hollow spheres gives rise to significant improvements in the cycling stability and rate performance of the TiO2 hollow spheres.